Impact of near continuous low dose rate neutron irradiation on pregnancy outcomes in mice - Jon G. Steller; Rebecca S. Blue; April E. Ronca; Andrew Goodspeed; Theresa L. Powell; Thomas Jansson (npj Microgravity)
Abstract The effects of galactic cosmic radiation on reproductive physiology remain largely unknown. We determined the impact of near-continuous low-dose-rate Californium-252 neutron irradiation (1 mGy/day) as a space-relevant analog on litter size and number of resorptions at embryonic day (E) 12.5 (n = 19 radiated dams, n = 20 controls) and litter size, number of resorptions, fetal growth, and placental signaling and transcriptome (RNA sequencing) at E18.5 (n = 21 radiated dams, n = 20 controls) in pregnant mice. A significantly increased early resorption rate and decreased placental weight were observed in irradiated mice. There were no statistically significant differences in litter size, fetal weight, length, or malformation rate between the groups. Near-continuous radiation had no significant effects on the mechanistic target of rapamycin (mTOR), endoplasmic reticulum stress or inflammatory signaling, rate of double-stranded DNA breaks, and had minimal effects on gene expression in the placenta. These data suggest that near-continuous, low-level galactic cosmic radiation has a limited impact on pregnancy outcomes.